Assessment of polypharmacy in elderly patients by using data from dispensed medications in community pharmacies: analysis of results by using different methods of estimation - Chiapella, Luciana Carla (2018)
Background Estimating the prevalence of polypharmacy is essential for the evaluation of public health. Many different methodologies are used to determine the number of drugs used by a patient. Objective To analyse and compare three different methods (simultaneous, cumulative and continuous medication) to determine the number of drugs used by a patient, to estimate the prevalence of polypharmacy and to evaluate the possible association between polypharmacy and the gender and age of patients. Method Cross-sectional observational study carried out between April and September 2015. Data were acquired from prescriptions corresponding to 3972 patients aged 65 years old or older in ten community pharmacies in Argentina. Results The prevalence of polypharmacy varied significantly according to the method used. Major polypharmacy (use of five or more drugs) was detected in 20.5–47.1% of the patients. The association between gender, age and polypharmacy was statistically significant only when using the continuous medication method. The prevalence of minor polypharmacy (use of two to four drugs) was similar with the three methods. Conclusion These results contribute to deciding which is the best method to determine polypharmacy according to the objective of future studies and considering the advantages and disadvantages of each of them.